Efficacy of Secukinumab in Moderate to Severe Psoriasis Vulgaris: A Prospective Study - Syeda Shahmoona Tirmizi, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Psoriasis is a chronic inflammatory skin disorder that potentially needs long-term treatment. Multiple remedies treating psoriasis have been accepted in which Secukinumab is a totally humanized, IL-17A monoclonal used for the treatment of moderate to severe plaque psoriasis. Hence, this study focused to evaluate the effectiveness of Secukinumab in moderate to severely affected psoriasis patients. Methodology: This was a Prospective interventional multicenter study conducted by using consecutive sampling technique. The ethical approval was approved from the Institutional Review Board. The duration of study was about one year after synopsis approval. A total of 138 adult patients between 18-65 years of both genders with diagnosed cases of psoriasis vulgaris having lesions on scalp, face, hands, and genital areas were included. Treatment started by the single dosage of 300 mg Secukinumab that was administered subcutaneously once weekly for 4 weeks and followed up by once a month for 52 weeks. Paired t-test was used to evaluate the association between baseline and at various weeks of follow ups. Results: The study results showed that out of 138 patients, 112(81.2%) were males and 26(18.8%) were females and their mean age was 40.47±9.55 years. As far as severity of Psoriasis is concerned, 55(39.9%) were moderately affected while 83(60.1%) were severely affected. Concerning distribution of Psoriasis, Plaque Psoriasis was observed in 117(84.8%) patients, 57(41.3%) reported Scalp Psoriasis, 137(99.3%) reported Pustular psoriasis, and Itching was reported in 120(87.0%) patients. Comparison of baseline PASI scores with different weeks in moderately and severely affected psoriasis patients revealed that there was statistically significant rapid reduction observed from mean of baseline PASI scores till 12 weeks (p<0.001), Conclusion: This study concluded that Secukinumab is an extremely effectual, rapid-acting biological therapy with no evident side effects. Furthermore, it was observed that secukinumab significantly reduced the baseline PASI score till 12 week rapidly in moderately and severely affected psoriasis patients. Keywords: Psoriasis vulgaris, PASI score, rapid-acting biological therapy, Secukinumab,